Longitudinal assessment of changes in muscle composition using proton density fat fraction and T2* in patients with and without incidental vertebral compression fractures - Yannick Stohldreier; Yannik Leonhardt; Jannik Ketschau; Florian T. Gassert; Marcus R. Makowski; Jan S. Kirschke; Georg C. Feuerriegel; Philipp Braun; Benedikt J. Schwaiger; Dimitrios C. Karampinos; Nina Hesse; Alexandra S. Gersing; et al. (Frontiers in Endocrinology)
ObjectiveChemical shift encoded-based water-fat separation magnetic resonance imaging (CSE-MRI) is an emerging noninvasive tool for the assessment of bone and muscle composition. This study aims to examine both the predictive value and the longitudinal change of proton density fat fraction (PDFF) and T2* in the paraspinal muscles (PSM) in patients with and without the development of an incidental vertebral compression fracture (VCFs) after 6 months of follow-up.MethodsPatients (N=56) with CT and 3T CSE-MRI of the lumbar spine at baseline and CSE-MRI at 6 months follow-up were included in this retrospective study. Patients who, on average, developed an incidental VCF one year after baseline MRI (VCF: N=14, 9 males, 66.8 ± 7.9 years) were frequency matched by age and sex to patients without VCFs (non-VCF) at baseline and follow-up (non-VCF: N=42, 27 males, 64.6 ± 13.3 years). Mean PDFF, T2*, and cross-sectional area (CSA) values from the autochthonous PSM of the thoracolumbar spine (T11-L4) and opportunistic CT-based bone mineral density (BMD) measurements were obtained for each individual. The associations between baseline measurements, longitudinal changes in PDFF, T2*, CSA of the PSM and the occurrence of VCFs at follow-up were evaluated using linear and logistic multivariable regression models. ROC analyses were used to assess cutoff values for predicting the development of VCFs.ResultsNo significant difference in PDFF of the PSM was found between the VCF and non-VCF group at baseline (VCF/non-VCF 8.5 ± 13.8% vs. 5.0 ± 4.6%; p=0.53). In multivariable linear regression models adjusted for sex, age and baseline BMD, PDFF values of the PSM increased significantly over 6 months in the VCF group (2.4 ± 2.8% vs. -1.0 ± 2.3%, p<0.001), while T2* values of the PSM showed a significant decrease (p ≤ 0.01). ROC analyses identified a PDFF increase of 0.2% in the PSM as the optimal cutoff value to distinguish between patients with and without VCF (AUC 0.86, 95% CI [0.74-0.98], p<0.001).ConclusionLongitudinal PDFF-based assessment of the PSM composition may be a useful indicator for the prediction of the development of vertebral compression fractures.